Adaptación y su incidencia en la integración escolar de los niños de primer año de educación básica del Jardín de Infantes Ciro Vicente Vera del cantón Pasaje, periodo lectivo 2010-2011. - Peñafiel Gallegos, Ana Marisol (2011)
This study is framed within the qualitative and quantitative analysis, which was conducted by the research in the first year of Basic Education Kindergarten Ciro Vera Vicente Canton Pasaje during the school year 2010 - 2011. This study overall objective to know the vision they have ranging from pre teachers, students / os, parents regarding the issue of adaptation and its impact on school integration, this the following specific objectives are derived: identifying the elements and aspects that influence the vision they have teaching regarding the issue of the integration of pupils and students of the school.